Adult molested as child - Babu, Namitha (Victimology, 2022)
Previous chapter focused on the sexual assault, and in continuation of that, this chapter mainly deals with the issue of being victim of sexual abuse in childhood. Children may not understand what is happening to them at that young age due to the developmental limitations in terms of cognitive and emotional aspects. They may comprehend the depth of incident and consequences later in their lives, and the chapter would focus on the emotional turmoil and the psychological and sexual problems among victims. The chapter also focuses on the later life problems experienced by sexual abuse victims and the effect on the quality of life. Adult victims of early onset abuse trauma experience life-long cardinal effects on the many aspects of life as well as demonstrate a change in brain structure and functions that are strong predictors of psychiatric morbidity. Physiological markers, mental health concerns, interpersonal relationships, socioeconomic facets, and issues around disclosure are some of the areas this chapter aims to address. The social and legal issues around the disclosure of the assault will be a part of this chapter. The forensic aspects of sexual assault crimes and the components involved in the conviction of a sexual abuse crime are discussed in this chapter. Also, the chapter aims to delineate the psychological trauma and flashbacks and how to deal with it. The various treatment modalities that address various psychological and psychiatric comorbidities are also elucidated.